2022
DOI: 10.3390/genes13061045
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Disorder and Alternative mRNA Splicing in Reward Circuitry

Abstract: Opiate/opioid use disorder (OUD) is a chronic relapsing brain disorder that has increased in prevalence in the last two decades in the United States. Understanding the molecular correlates of OUD may provide key insights into the pathophysiology of this syndrome. Using publicly available RNA-sequencing data, our study investigated the possible role of alternative mRNA splicing in human brain tissue (dorsal–lateral prefrontal cortex (dlPFC), nucleus accumbens (NAc), and midbrain) of 90 individuals with OUD or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A study evaluating mRNA alternative splicing in the human postmortem dlPFC, NAc, and midbrain associated with OUD identified eight differential spliced genes in morphine addiction ( 64 ), one of which was identified in our analysis: GABBR1 . In addition, they observed five spliced genes in the dlPFC, NAc, and ventral midbrain ( 64 ), including two genes with differential mCpHs found in our work: HERC1 and BIN1 . These results support an important gene regulatory role of OUD-linked differential mCpHs.…”
Section: Discussionmentioning
confidence: 91%
“…A study evaluating mRNA alternative splicing in the human postmortem dlPFC, NAc, and midbrain associated with OUD identified eight differential spliced genes in morphine addiction ( 64 ), one of which was identified in our analysis: GABBR1 . In addition, they observed five spliced genes in the dlPFC, NAc, and ventral midbrain ( 64 ), including two genes with differential mCpHs found in our work: HERC1 and BIN1 . These results support an important gene regulatory role of OUD-linked differential mCpHs.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, among our top findings, we found Bridging Integrator 1 ( BIN1 ) for which differential alternative splicing in the brain has been described in OUD. BIN1 was the only differential AS gene in OUD that was conserved across all investigated brain regions; dlPFC, NAc, and midbrain 26 . Further, AS events in Bin1 were identified in the mouse brain in a study on splicing alterations associated with cocaine self-administration 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified differential alternative splicing in alcohol use disorder 25 and opioid use disorder (OUD) 26 in the human brain, however, RNA splicing alterations have not been characterized in human CUD so far. In the differential alternative splicing analysis, we found N=98 statistically significant genes containing AS intron clusters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations